Effects of verbatim repetition of the headline message on the proceed button on click-through rates in online retail - Kutzner, Florian; Ermark, Florian K. G.; Fornoff, Julian; Wänke, Michaela (Frontiers in Psychology, 2024)
For online retailers, increasing click-through rates and reducing dropout are critical to success. In this study, we examine the effect of verbatim repetition of the website's headline message on the proceed button, based on research on processing fluency. We conducted a field study with 956 visitors to an online platform and found that verbatim repetitions of the header message on the proceed button resulted in a conversion rate increase of more than ten percentage points compared to gist repetitions and new messages. Our findings underscore the importance of simple verbatim features and demonstrate the successful application of processing fluency research to impact consumer behavior.